2022
DOI: 10.1111/odi.14275
|View full text |Cite
|
Sign up to set email alerts
|

Influence of periodontitis and diabetes on structure and cytokine content of platelet‐rich fibrin

Abstract: BackgroundPlatelet‐rich fibrin (PRF) is a second‐generation platelet concentrate with multiple applications in wound healing and regeneration in both periodontitis and diabetes. However, the three dimensional (3‐D) structure and cytokine content of PRF might be altered in patients suffering from either/both of the chronic inflammatory conditions, ultimately influencing the efficacy of PRF as a biomaterial for regenerative medicine.AimThe aim of the present study was hence to evaluate the effect of both these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The characteristics of autologous platelet concentrate are influenced by the age, health and nutrition status, autoimmunity, and genetic susceptibility of the individuals from which it originates [112, 113]. There is evidence showing that diabetes mellitus has an influence on the structure of platelet‐rich fibrin [112].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of autologous platelet concentrate are influenced by the age, health and nutrition status, autoimmunity, and genetic susceptibility of the individuals from which it originates [112, 113]. There is evidence showing that diabetes mellitus has an influence on the structure of platelet‐rich fibrin [112].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Gupta et al . [ 22 ] in a recent study proposed that PRF structure and cytokine profile may have been altered in patients suffering from periodontitis and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 , 28 ] However, studies have suggested that the reduced or compromised wound healing capacity in uncontrolled diabetic patients may be due to a reduction in growth factors and prolonged inflammatory responses due to increased proinflammatory cytokines in T2DM patients. [ 22 , 29 , 30 ] Thus, a modification in the protocol (rpm and time) for obtaining PRF in diabetic patients may be investigated. Recently, Surmeli Baran et al .…”
Section: Discussionmentioning
confidence: 99%